MIDDLE CHALCOLITHIC COPPER TOOLS FROM GÜLPINAR IN NORTH-WESTERN ANATOLIA – AN ARCHAEOMETRIC APPROACH - Güder, Ümit; Takaoğlu, Turan; Özdemir, Abdulkadir (Roemisch-Germanisches Zentralmuseum, 2021)
The prehistoric site of Gülpınar, located beneath the remains of the Graeco-Roman Sanctuary of Apollo Smintheus (Smintheion) in the coastal Troad, is one of those newly excavated sites that enhances our knowledge of the western Anatolian littoral and the adjacent eastern Aegean islands during the 5th millennium BC. One of the contributions of the archaeological excavations at the site is in the category of copper metallurgy, which is the point of focus of this study. Four copper tools (awls and pins) were revealed in phase III of Gülpınar, dated to between 4930 and 4455/4300 BC. Both the chemical composition and the microstructural features of these tools were examined to understand the metallurgical processes applied for their production and forming. Analytical techniques, portable X-ray fluorescence (p-XRF) analysis, metallography (optical microscopy), energy-dispersive X-ray spectroscopy (SEM-EDS) examination and micro-hardness testing were conducted on the available samples from the objects. The results of the archaeometric analyses demonstrated that the copper used to form these tools was obtained by heating and then smelting the sulphur-bearing polymetallic ores. In the chemical compositions, an amount of around 1% arsenic was detected. Although the arsenic content provided a moderate improvement in the physical properties of the tools, the amount was considered too low to demonstrate an intentional, controlled process for arsenic alloying. The metal of the tools may have been brought in semi-finished forms to Gülpınar, since no finds relating to the copper metallurgy (slag, crucibles, tuyeres) were encountered during the excavations. The forming was determined by applying cycles of heating, forging and annealing. Moreover, increasing the hardness of the tools by a final cold working process was also detected. © 2021 Roemisch-Germanisches Zentralmuseum. All rights reserved.
Objets en cuivre du Chalcolithique moyen de Gülpınar dans le Nord-Ouest de l’Anatolie – une approche archéométrique]; [Mittelchalkolithische Kupferwerkzeuge aus Gülpınar in Nordwestanatolien – ein archäometrischer Ansatz
Keywords: 5th millennium BC; archaeometry; copper tools; Gülpınar; North-Western Anatolia